The Effectiveness of Implementing Internship in Making A Professional Notary in Jepara District - Muhammad Nur Aklif; Aryani Witasari; Widhi Handoko (Jurnal Akta, 2020)
The implementation of internships for Notaries is very important, however, in reality the awareness of the Notary candidates has not been carried out effectively, this is due to the practicality of prospective Notaries who want to practice immediately so that not infrequently, the internships are not carried out according to the time set by the existing regulations. The method in this writing is descriptive analytical. Based on the available data, it is found that in fact the effectiveness of the extension of the internship period is 12 (twelve) months to 24 (twenty four) months depending on the intention of the prospective notary who interned himself. Some notaries experience difficulties and experience confusion when opening an office even though they have undergone an internship period of 24 (twenty four) months. This is because they do not take advantage of time and do not undergo apprenticeship activities properly. The absence of an internship implementation guideline and the absence of programs that must be undertaken during the apprenticeship makes the effectiveness of the internships back to each prospective notary who interns. So can be said that the ineffective implementation of the Notary's apprenticeship has resulted in a lack of experience and at the same time resulted in a lack of quality of Notaries in carrying out their functions and duties in the community, especially in the Jepara Regency area.